1972
DOI: 10.2172/4551381
|View full text |Cite
|
Sign up to set email alerts
|

Warm reinforcement and cold reinforcement magnet systems for Tokamak fusion power reactors: a comparison.

Abstract: Thli report wii prepired u in account of work •pomored by the United Stitei Government, Neither th* United Stitei nor the United Stitei Atomic Energy Commission, nor any of their employees, nor any of their contractors, lubcontrictori, or their employees, mikM any wimnty, express or implied, or auumei any 1»|«1 liibllKy or responiibllity for the accuracy, completeneu or uiefulneu of any Information, apparatui, product or proceu disclosed, or represents thit its use would not infringe privately owned rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…impossible.to replace the coil. In the second, the TF coil can be replaced, but the reactor is down for a long interval, e.g., 3 years, while massive replacement operations, involving movement of a large portion of the blanket and shield structure, vertical field coils, etc., are carried out.…”
Section: Intboduction : Applications and Advantages Of Dealsmentioning
confidence: 99%
“…impossible.to replace the coil. In the second, the TF coil can be replaced, but the reactor is down for a long interval, e.g., 3 years, while massive replacement operations, involving movement of a large portion of the blanket and shield structure, vertical field coils, etc., are carried out.…”
Section: Intboduction : Applications and Advantages Of Dealsmentioning
confidence: 99%
“…These coils do not require substantial precompression, however. Larger capacity coils, such as the ETM, are designed for warm earth support because the cost of cold support in larger systems is prohibitive [15].…”
mentioning
confidence: 99%
“…Los Alamos performed an economic analysis of SMES and concluded that a stainless steel structure required to contain the Lorentz forces wol,!d be prohibitively expensive [4]. Hassenzahl et al proposed replacing the traditional, external, stainless steel support structure which was housed within the cryostat and was referred to as a "cold structure" with a warm containment structure [5]. It was found that by building the magnet in situ in rock, significant cost savings could be realized.…”
mentioning
confidence: 99%